Land Snail Records from Missouri - Leslie Hubricht (Hello World!, 1972)
This paper lists all of the land snails from Missouri in the collection of the author. Fossil records are not included as these were published elsewhere (Sterkiana 13:7-17, 1964). Much more collecting needs to be done before the fauna of Missouri will be really known. There are very few records for northern Missouri. Only the area around St. Louis can be said to be thoroughly studied.